Evolutionary Ethics: Searching for the Sources of Altruism - Skujienė, Grita (Problemos, 2000)
“Altruism” is one of many concepts for expressing the content of morals. The article presents and overviews the main concepts of “altruism” by evolutionary ethics and presents analysis of the questions: What kind of phenomenon is altruism and what kind of relations has it with egoism? Is altruism as well as egoism given to us by nature or do we acquire it in the course of bringing up? In what way have the regulations of altruism consolidated in human society and what is the significant of it for a person? The author argues that at present altruism is identified with self-renunciations and sacrifice and this is an extreme interpretation of the subject. H. Spencer, the other followers of evolutionary ethics and sociobiologist claims that altruism is “all the conscious and unconscious actions that aim to save lives for the other individuals and from which suffer the doer's individual life”. Altruistic and egoistic quality lies deep in nature of a modem person as inherited quality’s expression of in which depend on level of the society the individual lives. Sacrifice of modem people in any extreme situations is the reflection of ancient need to preserve species, population, community: only the groups, members of which sacrificed for the sake of the whole group, survived. The author comes to the conclusions: 1. “Biological altruism” that we can find in all living communities is the origin of our ethical (moral) and social altruism. 2. With evolution of human consciousness, instinctive and natural human desire to help somebody in misfortune is gradually decreasing with conceiving of a number of valid excuses until an edge abatement of one’s own responsibility: when all saving work is leaving for the official State services. 3. The role of society and education for the expression of altruistic behaviour of a concrete person is negative: all the qualities related with altruism (for example, compassion, rightness, spontaneity and other) are gradually decreasing. This process excites a depression in the man's mentality and causes an increasing of senses of loneliness, of great anxiety and nonsense.